A model of recommended retail prices. (17th May 2017) - Lubensky, Dmitry
Abstract : Manufacturers frequently post nonbinding public price recommendations, but neither the rationale for this practice nor its impact on prices is well understood. I develop a model in which recommendations signal a manufacturer's production cost to searching consumers, who then form beliefs about retail prices. Increasing search makes consumers reject offers for the manufacturer's and competitors' products more often, and I show that both consumers and the manufacturer prefer more search when the production cost is low and less search when it is high. With incentives thus aligned, manufacturer recommendations inform consumers via cheap talk, and their removal harms both parties.